PENERAPAN HASIL BELAJAR DESAIN TEKSTIL PADA PRAKTEK PEMBUATAN ANYAMAN TAPESTRI - Citra Ayu Widianingsih; Supandi Supandi (Universitas Pendidikan Indonesia, 2016)
This research inspect about implementation of learning outcomes textile as a knowledge skill practice of making woven tapestry. The purpose of this research is to obtain data about learning outcomes textile review by basic knowledge of design motives, types of tapestries, tools and materials and implementation to practice of making woven tapestry. Research methods used is descriptive method that uses quantitative strategy. Samples used total sample amounted to 34 people. Means of collecting data using quesionnaires. Conclusions of this study indicate that implementation of learning outcomes “textile design” in terms of implementation to practice of tapestries, tools and materials and making of woven tapestry on textile engineering student class of 2011, most of the student are able to apply the material in the manufacture of woven textile design tapestry well.